Analyzing the personality traits of futsal players, - Yücel, A. S (My University, 2014)
Sport acts as a tool for individuals to understand and express their personalities better. Regarding “Personality and Sport”, while some scientists argue that individuals become successful by choosing the right sport for their personality, others suggest that individuals develop the personalities in line with the sport they choose. However, it is a matter to take into account that there may be different factors affecting the personality traits of athletes. The purpose of this research is to analyze the personality traits of athletes participating in Turkish futsal tournament held in Eskişehir in 2013 by such variables as sex and age, years in sport, the position and monthly income etc. Working group of the research is composed of 83 athletes who participated in Turkish futsal tournament held in Eskişehir in 2013. Data of the research were obtained by using “Eysenck Personality Questionnaire”. Descriptive statistics, reliability analysis, independent sample t-test, Anova analysis and Kruskal Wallis-H test, Man Whitney U test were utilized within the scope of analysis. According to the results obtained, it has been determined that the personality traits of the participants do not differ by age, habits of recreation and use of alcohol. Differences have been ascertained in dimensions of neuroticism by sex variable, psychoticism by the year in sport, extroversion by the position, neuroticism and psychoticism by the environment of being raised, neuroticism, lying and extroversion by income. Following the research, it has been concluded that some demographic characteristics of the participants result in differentiation in sub-dimensions of Eysenck personality questionnaire.
Makale - Bilimsel Dergi Makalesi - Tek Yazarlı
Keywords: Personality; Sport; Futsal